Product Characteristics and Qualities (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, special attention is paid to the concept of product quality, as well as its characteristics. Classification of quality indicators is given. Conclusions are made about the need to classify and study these indicators. Man comes into "possession of quality" in practical activity, consuming or using the corresponding products or services. For this reason, it is accepted that the starting point in the definition of quality is the value in use, which is the set of attributes that make a specific product useful to man.